Social values, criminal risks, and security - Fîrțală, Valeriu; Cristea, Darie (Technium Social Sciences Journal, 2023)
Compliance with the provisions of legal norms and prosocial conduct are directly related to the value system protected by these norms. The voluntary conformity of an individual to normative precepts is largely ensured by the consonance between the social values system to which significant majorities adhere in a society. The criminal risk increases as the values of the social group of belonging become more and more distant from the social values protected by normative acts. Such situations can be normal consequences of social change. The challenge posed by dissonances between formal and informal value systems has always been difficult for decision and policy makers to manage.